Consumers’ buying motive assessment tool: rational versus emotional - Roy, Mollika; Dash, Arobindu; Hossain, Muhammad Salim (Penerbit Universiti Kebangsaan Malaysia, 2018)
Now-a-days, understanding consumers’ buying motive is much more important for the marketers. As there is very limited literature in this field and no full version of psychometric tool are available for measuring consumer buying motive, we have taken initiative to develop ‘Consumers’ Buying Motive Assessment Tool’ (CBMAT). 388 early adult respondents were used in this study. In EFA, we found two-dimensional model of CBMAT having three factor at each dimension, comprising 26 items which explained 53.63% of sub-total variance of ‘Emotional’ dimension and 50.90% of sub-total variance of ‘Rational’ dimension. In both dimension, the reliability was high enough (Cronbach’s α of ‘Emotional’ = .826 and .837 for the ‘Rational’ dimension). We found high convergent validity within the same dimensional factors and high discriminant validity among different dimensional factors. By considering cutoff point (39), buyers’ motive can be low or high in both dimensions which comprises four types buyer motive such as ‘Equivocal’; ‘Utilitarian’; ‘Affective’ and ‘Indifferent’. These findings help to gain the psychometric properties of CBMAT which also support the ‘Dual Process Theory’. This study opens the door of further research on consumer buying motive.